ACCOUNTING AND MATERIALISM IN THE HISTORY OF IDEAS - Ratnam Alagiah (Jurnal Akuntansi Multiparadigma, 2012)
Abstract: Accounting and Materialism in the History of Ideas. Current popular culture is connected to the birth of a secular and materialistic interpretation of reality. Materialism, which is the tendency to be more concerned with material values through rational experimentation and discourse. This paper applies Foucault’s genealogy to explain that materialism is a product of a series of historical events that are closely related to the practice of accounting.  Second, accounting and “scientific materialism” have been instrumental in paving the course to their and our common failure. Third, the paper proposes a shift away from our impulse for a mere material existence leading to what has now become ‘popular culture’, to a vision of enhancing ‘an ever advancing civilization’. Abstrak: Akuntansi dan Materialisme dalam Sejarah Ide. Budaya populer saat ini terkait dengan kelahiran interpretasi realitas yang sekular dan materialistik. Materialisme yaitu kecenderungan untuk lebih peduli pada nilai-nilai material, melalui percobaan dan diskursus rasional.  Artikel ini menggunakan genealogi Foucault untuk menjelaskan bahwa materialisme adalah produk dari suatu seri kejadian-kejadian historis yang terkait erat dengan praktik akuntansi. Artikel ini menjelaskan bahwa akuntansi dan materialisme sains membentuk arah kegagalan kita. Artikel ini mengusulkan perpindahan paradogma dari sekadar eksistensi materialisme ke budaya populer, hingga suatu visi peradaban yang berkembang terus menerus.